Processing emotion from abstract art in frontotemporal lobar degeneration. (29th January 2016) - Cohen, Miriam H.; Carton, Amelia M.; Hardy, Christopher J.; Golden, Hannah L.; Clark, Camilla N.; Fletcher, Phillip D.; Jaisin, Kankamol; Marshall, Charles R.; Henley, Susie M.D.; Rohrer, Jonathan D.; Crutch, Sebastian J.; Warren, Jason D.
Abstract: Abstract art may signal emotions independently of a biological or social carrier: it might therefore constitute a test case for defining brain mechanisms of generic emotion decoding and the impact of disease states on those mechanisms. This is potentially of particular relevance to diseases in the frontotemporal lobar degeneration (FTLD) spectrum. These diseases are often led by emotional impairment despite retained or enhanced artistic interest in at least some patients. However, the processing of emotion from art has not been studied systematically in FTLD. Here we addressed this issue using a novel emotional valence matching task on abstract paintings in patients representing major syndromes of FTLD (behavioural variant frontotemporal dementia, n =11; sematic variant primary progressive aphasia (svPPA), n =7; nonfluent variant primary progressive aphasia (nfvPPA), n =6) relative to healthy older individuals ( n =39). Performance on art emotion valence matching was compared between groups taking account of perceptual matching performance and assessed in relation to facial emotion matching using customised control tasks. Neuroanatomical correlates of art emotion processing were assessed using voxel-based morphometry of patients' brain MR images. All patient groups had a deficit of art emotion processing relative to healthy controls; there were no significant interactions between syndromic group and emotion modality. Poorer art emotion valence matching performance was associated with reduced grey matter volume in right lateral occopitotemporal cortex in proximity to regions previously implicated in the processing of dynamic visual signals. Our findings suggest that abstract art may be a useful model system for investigating mechanisms of generic emotion decoding and aesthetic processing in neurodegenerative diseases. Highlights: Abstract art may signal emotions independently of a biological carrier. Processing of emotion from art has not been studied systematically in FTLD. We studied this using a novel emotion valence matching task on abstract paintings. Versus controls all major FTLD syndrome groups showed an art emotion deficit. Art emotion decoding correlated with grey matter in lateral occipitotemporal cortex.